Best Answer

Solve this system of equation using substitution 2x plus 6y equals 24 and 3x-2x equals 24 ?

Improved Answer:

2x+6y = 24

3x-2x = 24 => x =24

Substitute the value of x into the top equation to find the value of y:

48+6y = 24

6y = 24-48

6y = -24

y = -4

So: x = 24 and y = -4

Q: Solve this system of equation using substitution 2x plus 6y equals 24 and 3x-2x equals 24?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

You'd need another equation to sub in

You cant solve it unless it is an equation. To be an equation it must have an equals sign.

x+y=5

Since the second equation is already solved for "y", you can replace "y" by "9" in the other equation. Then solve the new equation for "x".

You use substitution when you can solve for one variable in terms of the others. By substituting, you remove one variable from the equation, which can then be solved. Once you solve for one variable, you can use substitution to find the other.

Related questions

You'd need another equation to sub in

You cant solve it unless it is an equation. To be an equation it must have an equals sign.

x+y=5

Since the second equation is already solved for "y", you can replace "y" by "9" in the other equation. Then solve the new equation for "x".

You use substitution when you can solve for one variable in terms of the others. By substituting, you remove one variable from the equation, which can then be solved. Once you solve for one variable, you can use substitution to find the other.

True

what is the solution of x-5y=10 and 2x-10y=20

-2

George saves nickels and dimes for tolls. If he has 8 coins worth $2.60,how many are nickels and how many are dimes? Answer this question by using system of equation.

The first step is to solve one of the equations for one of the variables. This is then substituted into the other equation or equations.

The easiest way to solve this system of equations is to solve for a variable in one of the equations. In the second equation, y = 3x. This can be substituted into the first equation: y = -4x - 7; 3x = = -4x - 7; 7x = -7; x = -1. Since we have determined that x equals -1, we can then substitute -1 into either equation to find our corresponding y-value. Thus: y = 3x; y = 3(-1) y = -3. Thus, the solution to this system of equations is (-1, -3).

by elimination,substitution or through the matrix method.